ISSR Analysis to Detect Genetic Variation Among Some Lentil Genotypes in Syria - Al-Mousa, Rehab; Alshaal, Alaa; Abbas, Shahinaz; Kountar, Khouzama (Al-Mukhtar Journal of Sciences, 2023)
Lentil (Lens culinaris Medik) plays a significant role in human and animal nutrition. It is important to generate baseline information on genetic diversity of local and introduced lentil in Syria. Therefore, this study aimed to assess diversity and relationship among two local varieties and 35 introduced lentil lines from ICARDA using 20 Inter Simple Sequence Repeats (ISSR) primers.18 primers were able to amplify DNA bands with a total of 184 bands. Primers ISSR5, ISSR11, ISSR13, ISSR15 and ISSR16 presented 100% polymorphism percentage. The mean value of polymorphism percentage was 87.31%. ISSR primers could identify 19 unique bands in all genotypes, 12 of them were positive bands (present) and 7 were negative bands (absent). Primer ISSR11 was able to detect 3 positive unique bands in genotype Ln20. The UPGMA (unweighted pair group method with arithmetical averages) clustering based on ISSR data grouped 37 lentil genotypes into 6 clusters. The lowest genetic distance (0.20) was observed between (Ln15 and Ln16, Ln21 and Ln22, Ln27 and Ln28) which proves that they are closely related. While Ln24 presented the highest genetic distance (0.49) with both Ln18 and Idleb3 which refers to their genetic divergence.